1996
DOI: 10.1002/j.1460-2075.1996.tb00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different roles for RanGDP and RanGTP in nuclear protein import.

Abstract: The importin‐alpha/beta heterodimer and the GTPase Ran play key roles in nuclear protein import. Importin binds the nuclear localization signal (NLS). Translocation of the resulting import ligand complex through the nuclear pore complex (NPC) requires Ran and is terminated at the nucleoplasmic side by its disassembly. The principal GTP exchange factor for Ran is the nuclear protein RCC1, whereas the major RanGAP is cytoplasmic, predicting that nuclear Ran is mainly in the GTP form and cytoplasmic Ran is in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
624
1
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 604 publications
(664 citation statements)
references
References 75 publications
28
624
1
5
Order By: Relevance
“…Furthermore, we observed that importin ␤ potentiates the binding of importin ␣ to GR ( Figure 3F). Similar results have been observed for the SV40 NLS (Rexach and Blobel, 1995;Gorlich et al, 1996). It will be interesting to determine the role that importin ␤ plays in this interaction, whether it simply stabilizes the importin ␣-GR NL1 interaction or can bind to NL1 directly.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, we observed that importin ␤ potentiates the binding of importin ␣ to GR ( Figure 3F). Similar results have been observed for the SV40 NLS (Rexach and Blobel, 1995;Gorlich et al, 1996). It will be interesting to determine the role that importin ␤ plays in this interaction, whether it simply stabilizes the importin ␣-GR NL1 interaction or can bind to NL1 directly.…”
Section: Discussionsupporting
confidence: 74%
“…Because importin ␤ binds importin ␣ and the importin ␣/importin ␤/SV40 NLS complex can be dissociated by RanQ69L (Rexach and Blobel, 1995;Gorlich et al, 1996), we investigated the role of importin ␤ in the binding of importin ␣ to the NL1 of GR. The presence of recombinant importin ␤ potentiated the binding of importin ␣ but not importin 7 to a purified GR fragment (407-556) containing NL1 ( Figure 3F, compare lanes 3-4 and 5-6), suggesting that importin ␤ plays an important role in importin ␣ but not importin 7 mediated GR nuclear import.…”
Section: ϩH) (B) Padh-n795mentioning
confidence: 99%
“…The predicted reduction in SAM biosynthesis and hypomethylation of pre-tRNAs might impede their proper folding and processing, as occurs in gcd10 and gcd14 mutants defective in methylation of m1A 58 (Anderson et al 1998;Calvo et al 1999). It is also interesting to note that Ran-dependent nucleocytoplasmic transport is dependent on both GTP-and GDPbound forms of the Ran GTPase, and that defects in tRNA maturation have been observed in nucleoporin mutants (Gorlich et al 1996;Sharma et al 1996;Izaurralde et al 1997). Hence, the abnormal GTP/ GDP ratio in the gua1-G388D mutant could contribute to the observed defects in tRNA maturation by interfering with Ran function.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly it has been suggested that Ran⅐GDP is the active form of the protein at the cytoplasmic side of the nuclear pore and that GTP-bound Ran is required to terminate translocation at the nucleoplasmic side with the Ran⅐GDP/GTP cycle providing directionality of transport. Evidence for this model includes the findings that Ran⅐GDP can bind to the NPC via its interaction with p10/NTF2, that a Ran mutant locked in the GTP-bound state fails to support nuclear protein import and prevents docking of an import substrate at the NPC, and that Ran⅐GTP can bind to importin ␤ thereby inducing the dissociation of importin ␣ from importin ␤ and most likely the termination of translocation (15,23,24).Genes encoding the principle regulators of the Ran GTPase cycle have also been shown to be essential for viability in budding and fission yeasts. In Saccharomyces cerevisiae and Schizosaccharomyces pombe, these genes encode the Ran homologues Gsp1p and spi1p (25,26), the RCC1 homologues Prp20p and pim1p (26,27), and the RanGAP homologues Rna1p and rna1p, respectively (28, 29).…”
mentioning
confidence: 99%
“…Accordingly it has been suggested that Ran⅐GDP is the active form of the protein at the cytoplasmic side of the nuclear pore and that GTP-bound Ran is required to terminate translocation at the nucleoplasmic side with the Ran⅐GDP/GTP cycle providing directionality of transport. Evidence for this model includes the findings that Ran⅐GDP can bind to the NPC via its interaction with p10/NTF2, that a Ran mutant locked in the GTP-bound state fails to support nuclear protein import and prevents docking of an import substrate at the NPC, and that Ran⅐GTP can bind to importin ␤ thereby inducing the dissociation of importin ␣ from importin ␤ and most likely the termination of translocation (15,23,24).…”
mentioning
confidence: 99%